Study of phenolic compounds of some members of the aster family (Asteraceae) - Tartynska, Ganna; Novosel, Olena; Kyslychenko, Viktoriia; Popyk, Andrii; Kuznetsova, Victoria (Annals of Mechnikov's Institute, 2023)
Introduction. Prospective sources of phenolic compounds are representatives of the aster family (Asteraceae) - the Сommon white or Сoltsfoot (Tussilago farfara L.) and New York aster (Symphyotrichum novi-belgii L.). According to literature data, Сoltsfoot leaves contain phenolic acids, chromones, flavonoids, and tannins [8]. In the traditional medicine of various countries of the world, Сoltsfoot is used to treat cough, respiratory diseases, inflammation of the lungs, allergies, diseases of the liver, cardiovascular system, gastrointestinal tract, diabetes, osteoporosis, neuropathy, neurodegenerative diseases, breast cancer and colon [8-10]. New York aster is used as an antipyretic, immunostimulant, diuretic, hemostatic, tonic, expectorant, diuretic, analgesic, tonic, antacid, antiseptic agent, in cosmetology for the treatment of skin inflammations. The roots are used for inflammatory diseases of the respiratory tract. The aim of the work was to study a comparative study of phenolic compounds of Сoltsfoot raw materials and New York aster. Materials and methods. Chemical reactions were used to detect flavonoids and tannins in the studied types of raw materials: cyanidin reaction in the modification according to Briant, with solutions of potassium hydroxide, ferrum (III) chloride, aluminum chloride, lead acetate (flavonoids), ferrum (III) ammonium sulfate, gelatin, quinine hydrochloride (tannins). The study of hydroxycinnamic acids and flavonoids was carried out by chromatography in a thin layer of sorbent with standard samples of hydroxycinnamic acids (chlorogenic, neochlorogenic, n-coumaric, caffeic acid) and flavonoids (rutin, quercetin, hyperoside, luteolin, apigenin) in the mobile phase formic acid anhydrous P - water R - methanol R - ethyl acetate R (2.5:4:4:50). A spectrometric method was used to determine biologically active substances in the studied raw materials. Determination of the quantitative content of hydroxycinnamic acids was carried out in accordance with the methodology of the State Pharmacopoeia of Ukraine (SPU) 2.0, volume 3, monograph "Leaves of NettleN"; the content of the sum of polyphenolic compounds was determined according to the DFU 2.0 method, volume 1, monograph "Determination of tannins in medicinal products of plant origin"; the content of flavonoids was determined according to the DFU 2.0 method, Appendix 1, monograph "Flowers of the pagoda tree". The study of catechins in Сoltsfoot leaves and New York aster herb was carried out by the method of high-performance liquid chromatography (HPLC) on an Agilent Technologies 1200 liquid chromatograph. Research results. The results of all the conducted reactions had a positive result, which indicated the presence of flavonoids and tannins in the studied types of raw materials. When carrying out the cyanidin reaction in the Briant modification with water-ethanol extracts of Сoltsfoot raw materials, the aqueous layer had a more intense red color compared to the organic one, which indicated the glycosidic nature of flavonoids. As a result of the reaction with a solution of iron (ІІІ) ammonium sulfate, the presence of tannins of the condensed group (black-green color) was established in the Сoltsfoot leaves, and hydrolyzable tannins (black-blue color) in the flowers and rhizomes. Well-known chemical reactions confirmed the presence of flavonoids in the studied raw material of New York aster. As a result of a chromatographic study, hydroxycinnamic acids and flavonoids were detected in all studied types of raw materials of Сoltsfoot and of New York aster. Among hydroxycinnamic acids, chlorogenic, neochorogenic, and caffeic acids were identified, and among flavonoids, rutin, quercetin, hyperoside, and luteolin were identified. As a result of the quantitative determination, it was established that the highest content of hydroxycinnamic acids and flavonoids was found in Сoltsfoot flowers – 2,73±0,09% and 1,93±0,07%, respectively. Сoltsfoot leaves dominated in the content of the sum of polyphenolic compounds – 4,88±0,15%. In Сoltsfoot rhizomes, the content of hydroxycinnamic acids and flavonoids was the lowest – 1,18±0,05% and 1,07±0,05%. The content of the sum of phenolic compounds in this type of Сoltsfoot raw material was 4,36±0,15%. Among the studied biologically active substances, the content of polyphenolic compounds and hydroxychoic acids was predominant in the roots of the New York aster, their content was 5,36±0,05% and 2,11±0,07%, respectively, while in the herb it was lower – 3,23±0 ,10% and 1,68±0,05%, respectively. Almost three times more flavonoids were accumulated in the New York aster than in the roots (3,61±0,02% and 0,86±0,03%, respectively). Analysis of the obtained data showed that 4 compounds were identified in both types of studied raw materials. Catechin prevailed in the content of Сoltsfoot leaves (949.17±18.98 μg/g), and epicatechinalate – in New York aster herb (575.32±11.51 μg/g). Among the identified compounds, epicatechin gallate in Сoltsfoot leaves (251.71±5.03 μg/g) and halocatechin in of New York aster herb had the lowest content (272.64±5.45 µg/g). The total content of catechins was slightly higher in Сoltsfoot leaves (1967.98±39.36 μg/g) compared to New York aster, where their sum was equal to 1900.46±38.01 μg/g. Conclusions. Quantitative content of: hydroxycinnamic acids, flavonoids, polyphenolic compounds in terms of pyrogallol was determined by the spectrophotometric method in the studied raw materials of Сoltsfoot and New York aster. It was established that polyphenolic compounds in terms of pyrogallol accumulated in the largest amount among the studied raw material samples. HPLC analysis showed that Сoltsfoot leaves and New York aster herb contained almost the same amount of catechin compounds, among which epicatechin gallate in Сoltsfoot leaves (251,71±5,03 μg/g) and halocatechin in New York aster herb (272,64±5,45 μg/g) had the highest content. Thus, the obtained data can be used in the standardization and development of quality control methods for plant raw materials.